Adhesive composite sheet

By controlling the ultraviolet absorption peak and peeling adhesive force change rate of the adhesive tape, the problem of residual glue pollution and insufficient heat resistance after high temperature use is solved, and efficient bonding, heat resistance and low pollution effects are achieved.

CN119842331APending Publication Date: 2025-04-18NITTO DENKO SHANGHAI SONGJIANG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311339497.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

After high temperature use, existing adhesive tapes are prone to contamination of residual glue on the surface of the adhesive body, and at the same time they are insufficient heat resistance.

Method used

By controlling the rate of change of the ultraviolet absorption peak of the adhesive layer of the adhesive sheet at a wavelength of 250 to 300 nm and the rate of change of peeling adhesive force at a stretching speed of 180° and 300 mm/min within a specific range, it ensures that the adhesive force attached to the Cu plate before and after high temperature treatment is basically unchanged.

Benefits of technology

Excellent adhesion, heat resistance and low pollution properties of the adhesive composite sheet are achieved, and peelability and operability are also significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842331A_ABST
    Figure CN119842331A_ABST
Patent Text Reader

Abstract

The invention provides an adhesive composite sheet. The adhesive composite sheet not only has excellent adhesiveness and heat resistance, but also does not cause residual adhesive pollution to an adherend, has excellent peelability and operability, and can be well applied to heat-resistant application fields such as heat-resistant protection or heat-resistant packaging processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composite sheet, and more particularly to an adhesive composite sheet having excellent adhesiveness, heat resistance and low contamination properties. Background Art

[0002] It is known that adhesive tapes are used to adhere to various adherend surfaces in various industrial fields to provide functions such as temporary fixation and heat-resistant protection, so adhesive tapes are widely used. However, conventional adhesive tapes have insufficient heat resistance and are prone to residual adhesive contamination on the adherend surface after being used at high temperatures, especially when peeled off after being adhered to the adherend surface.

[0003] Therefore, it is necessary to develop an adhesive tape that can reduce the above-mentioned defects and has excellent adhesion, heat resistance and low contamination. Summary of the invention

[0004] Problem that the invention aims to solve

[0005] The present invention is made to solve the above-mentioned conventional problems, and its object is to provide an adhesive composite sheet which not only has excellent adhesiveness and heat resistance but also does not cause residual adhesive contamination to the adherend and has low contamination.

[0006] Solutions for solving problems

[0007] The present inventors have conducted intensive research to solve the above problems and found that the change rate F of the peeling adhesive force of the adhesive composite sheet at the ultraviolet absorption peak in the wavelength range of 250 to 300 nm and the tensile speed of 180° and 300 mm / min to the Cu plate can be calculated by A / F B The present invention has been completed by controlling the adhesive strength of the adhesive sheet attached to the Cu plate to be within a specific range, that is, by keeping the adhesive strength substantially unchanged before and after the high temperature treatment, and thereby solving the above-mentioned problems.

[0008] That is, the present invention is as follows.

[0009] [1]. An adhesive composite sheet, comprising an adhesive layer,

[0010] The ultraviolet absorption peak of the adhesive composite sheet in the wavelength region of 250 to 300 nm is less than 0.22 abs.

[0011] The change rate F of the peeling adhesive force of the adhesive layer to the Cu plate at 180° and 300 mm / min tensile speed A / F B is less than 2,

[0012] Among them, F AThe adhesive strength is measured at 23°C after the adhesive layer is attached to a Cu plate and heated at 200°C for 1 hour.

[0013] F B The adhesive layer is bonded to a Cu plate and the adhesive strength is measured at 23°C.

[0014] [2] The adhesive composite sheet according to [1], wherein the surface energy of the adhesive layer at 23° C. is 20 to 30 mN / m.

[0015] [3] The adhesive composite sheet according to [1] or [2], wherein the adhesive layer is formed from an adhesive composition,

[0016] The adhesive composition comprises a base polymer, which comprises, based on 100 parts by weight of all monomer components of the base polymer, 70 to 90 parts by weight of a soft monomer, 5 to 20 parts by weight, preferably 5 to 10 parts by weight of a monomer represented by the following formula (a) or by the following formula (b), and 5 to 12 parts by weight of a functional monomer.

[0017]

[0018] In formula (a), X1 represents -NH-R, wherein R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms;

[0019] A means that the terminal group contains a C=C side chain;

[0020]

[0021] In formula (b), X2 represents -NH;

[0022] A represents a side chain having one C=C at the terminal group.

[0023] [4] The adhesive composite sheet according to [3], wherein the base polymer satisfies any one of the following conditions (i) to (iii):

[0024] (i) the soft monomer is a (meth)acrylate monomer represented by the following formula (c) having a glass transition temperature of -80 to -10°C,

[0025]

[0026] In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms,

[0027] Y represents a hydrogen atom or a methyl group;

[0028] (ii) the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-hydroxymethylmethacrylamide and 2-[[(butylamino)-carbonyl]oxy]ethyl 2-acrylate,

[0029] The monomer represented by formula (b) comprises 2-acrylic acid-2-(2-oxo-1-imidazolinyl)ethyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)ethyl ester, 2-acrylic acid-2-(2-oxo-1-imidazolinyl)propyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)propyl ester, 2-acrylic acid-2-(2-oxo-1-imidazolinyl)butyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)butyl ester, N-[2- at least one of the group consisting of 2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide and 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide;

[0030] (iii) the functional monomer comprises a (meth)acrylate monomer containing a hydroxyl group and / or a (meth)acrylate monomer containing a carboxyl group,

[0031] The hydroxyl-containing (meth)acrylate monomer comprises at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate,

[0032] The carboxyl-containing (meth)acrylate monomer comprises at least one selected from the group consisting of (meth)acrylic acid, (iso)butylene acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate and 2-carboxypentyl (meth)acrylate.

[0033] [5] The adhesive composite sheet according to [3], wherein the adhesive composition further comprises a cross-linking agent;

[0034] Preferably, based on 100 parts by weight of the base polymer, the content of the crosslinking agent is 2 to 20 parts by weight, preferably 2 to 15 parts by weight.

[0035] Preferably, the cross-linking agent comprises an amino resin cross-linking agent.

[0036] [6] The adhesive composite sheet according to [1] or [2], wherein the adhesive composite sheet satisfies any one of the following conditions (iv) to (viiii):

[0037] (iv) the thermal weight loss of the adhesive layer at 200° C. is 1.0% or less, preferably 0.6% or less;

[0038] (v) the adhesive layer has a gel fraction of 20 to 70% when measured at 23° C. after being heated at 150° C. for 2 hours;

[0039] (vi) The adhesive layer is bonded to a Cu plate and left at 23°C x 50% RH for 0.5 h before measuring the adhesive strength F. B 0.5-3.5N / 20mm, preferably 0.5-2N / 20mm;

[0040] (vii) The adhesive layer is attached to a Cu plate, heated at 200°C for 1 hour, and then placed at 23°C x 50% RH for 0.5 hour to measure the adhesive strength F. A 10N / 20mm or less, preferably 5N / 20mm or less;

[0041] (viii) after the adhesive layer is attached to the Cu plate and peeled off, the surface energy of the Cu plate is 30 to 40 mN / m;

[0042] (viiii) The elastic modulus change rate W of the adhesive layer when pressed into 500 nm by nanoindentation at 23° C. and 100 Hz B / W A 1.1~3.5,

[0043] Among them, the elastic modulus W A is the elastic modulus of the adhesive layer at 23°C,

[0044] Elastic modulus W B It is the elastic modulus of the adhesive layer at 23°C after being heated at 150°C for 2 hours.

[0045] [7] The adhesive composite sheet according to [1] or [2], wherein the thickness of the adhesive layer is 2 to 200 μm.

[0046] [8] The adhesive composite sheet according to [1] or [2], further comprising a substrate layer, the substrate layer being disposed on one side of the adhesive layer;

[0047] The substrate layer includes a polyethylene oxide film (PO film), a polyimide film (PI film), a polyethylene terephthalate film (PET film), a polypropylene film (PP film) or a polyethylene film (PE film);

[0048] The thickness of the substrate layer is 2 to 50 μm.

[0049] Effects of the Invention

[0050] The adhesive composite sheet of the present invention has excellent adhesiveness and heat resistance, and does not cause residual adhesive pollution to the adherend, and has excellent peelability and operability. When the adhesive composite sheet is used in heat-resistant protection or heat-resistant packaging processes, it will not be significantly increased or decreased due to thermal degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to one embodiment of the present invention.

[0052] Figure 2 It is a diagram schematically showing the evaluation of the permeability of the encapsulating resin.

[0053] Description of Reference Numerals

[0054] 1 Bonding composite sheet

[0055] 10. Base material layer

[0056] 20 Adhesive layer DETAILED DESCRIPTION

[0057] The following describes a suitable embodiment of the present invention. Matters necessary for implementing the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the field.

[0058] In addition, in the following drawings, the same symbols are sometimes used to mark the components and parts that play the same role, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments recorded in the drawings are schematically illustrated to clearly illustrate the present invention and do not necessarily accurately represent the size and scale of the actual product provided.

[0059] <Adhesive Composite Sheet>

[0060] The adhesive composite sheet of the present invention comprises a substrate layer and an adhesive layer disposed on one side of the substrate layer, wherein the ultraviolet absorption peak of the adhesive composite sheet in the wavelength region of 250 to 300 nm is less than 0.22 abs, and the rate of change F of the peeling adhesive force of the adhesive layer to the Cu plate at a tensile speed of 180° and 300 mm / min is A / F B is less than 2,

[0061] Among them, F A The adhesive strength is measured at 23°C after the adhesive layer is attached to a Cu plate and heated at 200°C for 1 hour.

[0062] F B The adhesive layer is bonded to a Cu plate and the adhesive strength is measured at 23°C.

[0063] Figure 1 : is a cross-sectional view schematically showing the structure of an adhesive composite sheet according to one embodiment of the present invention. Figure 1 As shown, the adhesive composite sheet 1 includes a substrate layer 10 and an adhesive layer 20 provided on one side of the substrate layer 10 . The adhesive layer 20 is preferably provided on the entire surface of the substrate layer 10 .

[0064] Although not shown in the figure, the pressure-sensitive adhesive composite sheet of the present invention may be provided with a release liner on the outside of the pressure-sensitive adhesive layer for the purpose of protecting the pressure-sensitive adhesive surface before use.

[0065] The concept of adhesive composite sheet mentioned in this specification may include objects called adhesive sheets, adhesive tapes, adhesive labels, adhesive films, etc. It should be noted that the adhesive composite sheet disclosed herein may be a single sheet or an adhesive sheet further processed into various shapes. In some preferred embodiments, the adhesive composite sheet of the present invention may be provided in a long strip.

[0066] The adhesive composite sheet of the present invention has the following characteristics:

[0067] The ultraviolet absorption peak of the adhesive composite sheet in the wavelength region of 250 to 300 nm is less than 0.22 abs. When the ultraviolet absorption peak in the wavelength region of 250 to 300 nm is within the above range, the monomer represented by formula (a) or by formula (b) can undergo a cross-linking reaction with the functional monomer to generate a cross-linking group, and the cohesive force is increased. The adhesive composite sheet has both excellent adhesion and heat resistance, and will not cause residual adhesive pollution to the adherend.

[0068] The ultraviolet absorption peak in the wavelength region of 250 to 300 nm can be measured, for example, by the method described in the Examples described later.

[0069] The change rate F of the peeling adhesive force of the adhesive layer to the Cu plate at 180° and 300 mm / min tensile speed A / F B is less than 2, where F A The adhesive layer is laminated to a Cu plate, heated at 200°C for 1 hour, and then measured at 23°C. B The adhesive layer is bonded to a Cu plate and the adhesive strength is measured at 23°C.

[0070] In some preferred embodiments, the rate of change F of the peeling adhesion of the adhesive layer to the Cu plate at 180° and 300 mm / min tensile speed is A / F B It is preferably 1.9 or less, more preferably 1.8 or less, further preferably 1.7 or less, still further more preferably 1.6 or less.

[0071] In some preferred embodiments, the rate of change F of the peeling adhesion of the adhesive layer to the Cu plate at 180° and 300 mm / min tensile speed is A / F B Preferably, it is 1 or more.

[0072] The adhesive force can be measured, for example, by the method described in Examples below.

[0073] When the surface energy of the adhesive layer at 23°C and the rate of change of the peel adhesion to the Cu plate at 180° and 300 mm / min tensile speed F A / F B When the amount falls within the above ranges, the adhesive composite sheet can have both excellent adhesiveness and heat resistance, and will not cause residual adhesive contamination to the adherend, and has excellent peelability and handleability.

[0074] When the change rate of peeling adhesive force is too large, the adhesive composite sheet is easy to break when peeling, and the adhesive layer is easy to remain on the surface of the adhered object to cause pollution. If the change rate of peeling adhesive force is too small, the adhesive composite sheet is easy to warp or fall off, and lose its shielding and protective functions.

[0075] In some preferred embodiments, the surface energy of the adhesive layer at 23°C is 20-30 mN / m, with a lower limit of preferably 21 mN / m, more preferably 22 mN / m, further more preferably 23 mN / m, still further more preferably 24 mN / m, and an upper limit of preferably 29.5 mN / m, more preferably 29 mN / m, further more preferably 28.5 mN / m, still further more preferably 28 mN / m.

[0076] When the surface energy is out of the above range, the adhesive layer may contaminate the surface of the adhered object.

[0077] The surface energy can be measured, for example, by the method described in Examples below.

[0078] [Adhesive layer]

[0079] The adhesive layer of the present invention comprises a base polymer. The adhesive layer in the technology disclosed herein can be a layer formed by an adhesive composition comprising a base polymer. The form of the adhesive composition is not particularly limited, and for example, it can be an adhesive composition of various forms such as a water-dispersible type, a solvent type, a hot melt type, an active energy ray-curable type (e.g., a photocurable type).

[0080] Hereinafter, each component of the adhesive composition of the present invention will be described in detail.

[0081] (Base polymer)

[0082] The adhesive composition of the present invention comprises a base polymer. As the base polymer, for example, an acrylic polymer, a rubber polymer, a polyester polymer, a urethane polymer, a polyether polymer, a silicone polymer, a polyamide polymer, a fluorine polymer, etc. can be included. Preferably, the adhesive composition comprises an acrylic polymer as the base polymer.

[0083] There is no particular restriction on the content of the base polymer. From the viewpoint of obtaining sufficient bonding reliability, it is preferably 70% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more relative to the total amount of the adhesive composition (total mass, 100% by mass). By adjusting the content of the base polymer in the adhesive composition to within the above range, an adhesive composition having better stress relaxation and durability and excellent adhesion to an adherend can be provided.

[0084] The base polymer in the technology disclosed herein is preferably a polymer comprising the following monomer components: based on 100 parts by weight of all monomer components of the base polymer, the base polymer comprises: 70 to 90 parts by weight of a soft monomer, 5 to 20 parts by weight, preferably 5 to 10 parts by weight of a monomer represented by the following formula (a) or by the following formula (b), and 5 to 12 parts by weight of a functional monomer,

[0085]

[0086] In formula (a), X1 represents -NH-R, wherein R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms;

[0087] A means that the terminal group contains a C=C side chain;

[0088]

[0089] In formula (b), X2 represents -NH;

[0090] A represents a side chain having one C=C at the terminal group.

[0091] In a preferred embodiment, the soft monomer comprises an alkyl (meth)acrylate. In the present specification, the term "alkyl (meth)acrylate" refers to an alkyl acrylate and / or an alkyl methacrylate.

[0092] As the alkyl (meth)acrylate, an alkyl (meth)acrylate having an alkyl group with 3 to 20 carbon atoms is preferred. Specific examples of the alkyl (meth)acrylate having an alkyl group with 3 to 20 carbon atoms are not particularly limited, and include propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2-EHA) are preferred. The (meth)acrylic acid alkyl esters may be used alone or in combination of two or more.

[0093] In some preferred embodiments, the soft monomer is preferably a (meth)acrylate monomer having a glass transition temperature of -80 to -10°C represented by the following formula (c):

[0094]

[0095] In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms,

[0096] Y represents a hydrogen atom or a methyl group.

[0097] Examples of the alkyl group having 3 to 20 carbon atoms represented by Z include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, 2-ethylhexyl, heptyl, octyl, isooctyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, or eicosyl.

[0098] Examples of the cycloalkyl group having 3 to 20 carbon atoms represented by Z include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclodecyl, cyclododecyl, 4-methylcyclohexyl, and 4-ethylcyclohexyl.

[0099] Examples of the (meth)acrylate monomer represented by formula (c) having a glass transition temperature of -80 to -10°C include 2-ethylhexyl acrylate (Tg: -70°C) and n-butyl acrylate (Tg: -55°C).

[0100] Based on 100 parts by weight of all monomer components of the acrylic polymer, the content of the soft monomer is preferably 70 to 90 parts by weight, more preferably 75 to 89 parts by weight. In some specific embodiments, based on 100 parts by weight of all monomer components of the acrylic polymer, the content of the soft monomer is preferably 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight or 90 parts by weight. When the content of the soft monomer is within the above range, excellent adhesion can be obtained.

[0101] In the monomer represented by formula (a), X1 represents -NH-R, wherein R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms.

[0102] Examples of the alkyl group having 1 to 6 carbon atoms represented by R include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, and hexyl.

[0103] Examples of the cycloalkyl group having 3 to 20 carbon atoms represented by R include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclodecyl, cyclododecyl, 4-methylcyclohexyl, and 4-ethylcyclohexyl.

[0104] The heteroatom in the heterocyclic group having 3 to 20 carbon atoms represented by the above R is preferably selected from N, O and / or S. In the present invention, the number of heteroatoms may be 1 or more. Examples of the heterocyclic group having 3 to 20 carbon atoms represented by the above R include: propiolactone group, lactam group, maleic anhydride group, tetrahydrofuranyl group, furanyl group, thienyl group, pyrrolyl group, thiazolyl group, pyridyl group, pyrimidyl group, quinolyl group, indolyl group, purinyl group, and the like.

[0105] In some preferred embodiments, the monomer represented by formula (a) is preferably a monomer represented by the following formula (a1),

[0106]

[0107] In formula (a1), Ra1 represents a hydrogen atom or a methyl group; Ra2 represents an alkyl group having 1 to 6 carbon atoms or -Ra4-Ra5; Ra3 represents an alkyl group having 1 to 6 carbon atoms or a hydrogen atom; Ra4 represents an alkyl group having 1 to 6 carbon atoms; Ra5 represents or a hydroxyl group; Ra6 represents an alkyl group having 1 to 6 carbon atoms; Ra7 represents an alkyl group having 1 to 6 carbon atoms.

[0108] Examples of the alkyl group having 1 to 6 carbon atoms represented by the above Ra2 to Ra4 and Ra6 to Ra7 include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl and hexyl.

[0109] In some preferred embodiments, the monomer represented by formula (a) is preferably a monomer represented by the following formula (a2),

[0110]

[0111] In formula (a2), Ra8 represents an alkylene group having 1 to 6 carbon atoms; Ra9 represents an alkyl group having 1 to 6 carbon atoms.

[0112] Examples of the alkylene group having 1 to 6 carbon atoms represented by Ra8 include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a pentylene group, and a hexylene group.

[0113] Examples of the alkyl group having 1 to 6 carbon atoms represented by Ra9 include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, and hexyl.

[0114] In some preferred embodiments, the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-hydroxymethylmethacrylamide and 2-[[(butylamino)-carbonyl]oxy]ethyl 2-acrylate.

[0115] The monomer represented by the above formula (b) is preferably selected from the group consisting of 2-(2-oxo-1-imidazolinyl)ethyl 2-acrylate, 2-(2-oxo-1-imidazolinyl)ethyl 2-methyl-2-acrylate, 2-(2-oxo-1-imidazolinyl)propyl 2-acrylate, 2-(2-oxo-1-imidazolinyl)propyl 2-methyl-2-acrylate, 2-(2-oxo-1-imidazolinyl)butyl 2-acrylate, 2-(2-oxo-1-imidazolinyl)butyl 2-methyl-2-acrylate, N-[ At least one of the group consisting of 2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide and 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide.

[0116] Based on 100 parts by weight of all monomer components of the acrylic polymer, the content of the monomer represented by formula (a) or represented by formula (b) is preferably 5 to 20 parts by weight, and more preferably 5 to 10 parts by weight. In some specific embodiments, based on 100 parts by weight of all monomer components of the acrylic polymer, the content of the monomer represented by formula (a) or represented by formula (b) is preferably 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight or 20 parts by weight. When the content of the monomer represented by formula (a) or represented by formula (b) is within the above range, the high temperature self-polymerization characteristics of the acrylic polymer can be improved, thereby obtaining excellent heat resistance.

[0117] As the functional monomer, a monomer having a polar group can be suitably used. The monomer having a polar group is useful for introducing a crosslinking point into the base polymer or increasing the cohesive force of the base polymer. The functional monomer can be used alone or in combination of two or more.

[0118] Specific non-limiting examples of the functional monomer include hydroxyl group-containing monomers and / or carboxyl group-containing monomers.

[0119] The content of the functional monomer is preferably 5 to 12 parts by mass, more preferably 6 to 11 parts by mass, based on 100 parts by mass of all monomer components of the acrylic polymer. When the content of the functional monomer is within the above range, the cohesive force of the adhesive can be prevented from becoming too high, and the adhesiveness can be improved.

[0120] A hydroxyl-containing monomer refers to a monomer having at least one hydroxyl group in the molecule. When the monomer component used to constitute the acrylic polymer includes a hydroxyl-containing monomer, that is, when the acrylic polymer includes a monomer unit derived from a hydroxyl-containing monomer, the cohesive force of the acrylic polymer is improved due to the formation of secondary bonds such as hydrogen bonds with the adherend, and the change in adhesive force over time can be more effectively suppressed. There is less residual adhesive on the adherend after peeling, and it has higher aggregation. The acrylic polymer of this embodiment can use one hydroxyl-containing monomer, or two or more hydroxyl-containing monomers.

[0121] As the hydroxyl group-containing monomer, a (meth)acrylate monomer containing a hydroxyl group is preferred.

[0122] Specific examples of hydroxyl-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.

[0123] There is no particular limitation on the content of the hydroxyl-containing monomer. For example, the content of the hydroxyl-containing monomer is 0.5 to 6 parts by mass, preferably 0.5 to 5 parts by mass, based on 100 parts by mass of all monomer components of the acrylic polymer. When the content of the hydroxyl-containing monomer is within the above range, the cohesive force of the acrylic polymer is improved due to the formation of secondary bonds such as hydrogen bonds with the adherend, which can more effectively suppress the change of the adhesive force over time, and there is less residual adhesive on the adherend after peeling, and the agglomeration property is higher.

[0124] A carboxyl group-containing monomer refers to a monomer having at least one carboxyl group in the molecule. When the raw material monomer of the acrylic polymer contains a carboxyl group-containing monomer, the cohesive force of the acrylic polymer is improved due to the formation of secondary bonds such as hydrogen bonds with the adherend, and the change of the adhesive force over time can be more effectively suppressed. Moreover, less residual adhesive is left on the adherend after peeling, and the agglomeration property is higher.

[0125] As the carboxyl group-containing monomer, a (meth)acrylate monomer containing a carboxyl group is preferred.

[0126] As specific examples of carboxyl-containing monomers, for example, (methyl) acrylic acid, (iso) butylene acid, (cis / trans)-2-methyl-2-butylene acid, 2-butylene acid isomethyl ester, 2-butylene acid isoethyl ester, 2-butylene acid isopropyl ester, 2-butylene acid isobutyl ester, (methyl) acrylic acid-2-carboxyethyl ester, (methyl) acrylic acid-2-carboxypropyl ester, (methyl) acrylic acid-2-carboxybutyl ester and (methyl) acrylic acid-2-carboxypentyl ester can be used alone. Any one of the above carboxyl-containing monomers can be used alone or in combination of two or more.

[0127] The content of the carboxyl group-containing monomer is not particularly limited, for example, based on 100 parts by mass of all monomer components of the acrylic polymer, the content of the carboxyl group-containing monomer is preferably 1 to 10 parts by mass. When the content of the carboxyl group-containing monomer is within the above range, the cohesive force of the acrylic polymer is improved due to the formation of secondary bonds such as hydrogen bonds with the adherend, and the change of the adhesive force over time can be more effectively suppressed, and there is less residual adhesive on the adherend after peeling, and the agglomeration property is higher.

[0128] The method for obtaining the acrylic polymer is not particularly limited, and various known polymerization methods such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization can be appropriately used. For example, solution polymerization can be preferably used. As a monomer supply method for solution polymerization, a batch feeding method of supplying all monomer raw materials at once, a continuous supply (drip) method, a divided supply (drip) method, etc. can be appropriately used. The polymerization temperature when performing solution polymerization can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be set to, for example, about 20 to 170°C (typically about 40 to 140°C).

[0129] The solvent (polymerization solvent) used in solution polymerization can be appropriately selected from existing known organic solvents. For example, any one solvent or a mixed solvent of two or more selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (e.g. monohydric alcohols with 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone, etc. can be used.

[0130] The initiator used in the polymerization can be appropriately selected from the existing known polymerization initiators according to the type of polymerization method. For example, one or more of the azo polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN) can be preferably used. As other examples of polymerization initiators, there can be listed: persulfates such as potassium persulfate; peroxide initiators such as benzoyl peroxide and hydrogen peroxide; substituted ethane initiators such as phenyl substituted ethane; aromatic carbonyl compounds, etc. As other examples of polymerization initiators, redox initiators obtained by combining peroxides and reducing agents can be listed. Such polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is the usual amount, for example, it can be selected from the range of about 0.005 mass parts to about 1 mass part (typically about 0.01 mass parts to about 1 mass part) relative to 100 mass parts of all monomer components.

[0131] The weight average molecular weight (Mw) of the base polymer (preferably an acrylic polymer) in the technology disclosed herein is not particularly limited, and may be, for example, 1,000,000 or less, preferably 400,000 or more. Generally, when the weight average molecular weight Mw exceeds 1,000,000, the cohesive force tends to increase due to the effect of polymer entanglement, thereby reducing fluidity, and sometimes a sufficient bonding area cannot be obtained, and the adherend cannot be fixed.

[0132] Here, the weight average molecular weight (Mw) refers to a value converted to standard polystyrene obtained by gel permeation chromatography (GPC). For example, a GPC apparatus can be used with the model name "HLC-8320GPC" (column: TSKgelGMH-H(S), manufactured by Tosoh Corporation).

[0133] (Crosslinking agent)

[0134] In the present invention, the adhesive composition preferably contains a crosslinking agent in order to adjust cohesive force and the like.

[0135] As the crosslinking agent, it is preferred to include an amino resin crosslinking agent, etc. By using the crosslinking agent, a moderate crosslinking reaction can be generated, the cohesive force can be fully improved, good adhesion can be ensured, and the generation of residual adhesive during the peeling operation can be effectively prevented.

[0136] Examples of the amino resin crosslinking agent include butylated melamine-formaldehyde resin, benzoguanamine, methylated methylol urea, methylated methylol N,N-ethylene urea, methylated methylol dicyandiamide, methylated methylol melamine, methylated methylol benzoguanamine, butylated methylol melamine, and butylated methylol benzoguanamine.

[0137] In the present invention, in addition to the amino resin crosslinking agent, the crosslinking agent may also optionally include a crosslinking agent such as an isocyanate crosslinking agent, an epoxy crosslinking agent, and the like.

[0138] The amount of the crosslinking agent used is preferably 2 to 20 parts by weight, preferably 2 to 15 parts by weight, relative to 100 parts by weight of the base polymer. By setting the amount of the crosslinking agent to the above range, the cohesive force of the adhesive can be increased, residual adhesive can be prevented from being generated on the adherend, and the heat resistance of the adhesive composite sheet can also be improved. In some embodiments, from the viewpoint of avoiding the decrease in viscosity caused by excessive increase in cohesive force, the amount of the crosslinking agent used relative to 100 parts by weight of the base polymer is more preferably 13 parts by weight or less, and further preferably 12 parts by weight or less.

[0139] In order to more effectively carry out the above crosslinking reaction, a crosslinking catalyst may also be used. As the crosslinking catalyst, for example, a tin catalyst (for example, dioctyltin dilaurate) may be preferably used. The amount of the crosslinking catalyst used is not particularly limited, and for example, is preferably 0.0001 to 1 part by mass relative to 100 parts by mass of the base polymer.

[0140] In addition to the above-mentioned components, the adhesive composition of the present invention may contain various additives commonly used in the adhesive field such as photoinitiators, plasticizers, softeners, antioxidants, and antioxidants as needed within the range that does not impair the effects of the present invention. Regarding such various additives, conventionally known additives can be used by conventional methods.

[0141] (Formation of Adhesive Layer)

[0142] Adhesive layer disclosed here can be formed by existing known method.For example, can adopt by directly applying (typically coating) adhesive composition to this substrate layer and make it dry and form the method (direct method) of adhesive layer.In addition, can also adopt by applying adhesive composition to the surface (peeling surface) with peelability and make it dry and form adhesive layer on this surface and the method (transfer method) that this adhesive layer is transferred to the substrate layer.Consider from the viewpoint of productivity, preferred transfer method.As above-mentioned peeling surface, can utilize the surface of release liner, the substrate layer back side that has carried out peeling process etc.It should be noted that, adhesive layer disclosed here typically is formed continuously, but is not limited to such form, can also be formed as the adhesive layer of regular or irregular pattern such as point shape, stripe shape for example.

[0143] The adhesive composition can be applied using a conventionally known coater such as a gravure roll coater, a die coater, or a bar coater. Alternatively, the adhesive composition can be applied by impregnation or curtain coating.

[0144] From the viewpoint of promoting the crosslinking reaction and improving the manufacturing efficiency, the drying of the adhesive composition is preferably carried out under heating. The drying temperature can be set to about 40 to 150° C., for example, and is usually preferably set to about 60 to 130° C. After the adhesive composition is dried, it can be further aged for the purpose of regulating the migration of components in the adhesive layer, carrying out the crosslinking reaction, and relaxing the strain that may exist in the substrate layer or the adhesive layer.

[0145] The thickness of the adhesive layer is not particularly limited, but is preferably 2 to 200 μm in consideration of the balance between adhesion to an adherend and cohesion. By setting the thickness of the adhesive layer within the above range, good adhesion and high temperature resistance can be achieved.

[0146] (Characteristics of Adhesive Layer)

[0147] The adhesive layer of the present invention has the following characteristics:

[0148] In some preferred embodiments, the thermal weight loss of the adhesive layer when heated from 40° C. to 200° C. at a heating rate of 10° C. / min is 1.0% or less, preferably 0.6% or less.

[0149] When the thermal weight loss rate of the adhesive layer is within the above range, a bonded composite sheet with better heat resistance can be provided. When the bonded composite sheet is used in a heat-resistant protection or heat-resistant packaging process, the cohesive force will not be significantly increased or decreased due to thermal degradation, or will not be reduced.

[0150] The thermal weight loss can be measured, for example, by the method described in Examples below.

[0151] In some preferred embodiments, the gel fraction of the adhesive layer measured at 23° C. after being heated at 150° C. for 2 hours is 20 to 70%. When the gel fraction is within the above range, excellent adhesive properties can be obtained. The gel fraction can be adjusted, for example, by selecting the composition and molecular weight of the acrylic polymer, the presence or absence of a crosslinking agent, its type, and the amount of the crosslinking agent.

[0152] The gel fraction can be measured by, for example, the method described in Examples below.

[0153] In some preferred embodiments, the adhesive layer is attached to a Cu plate and the adhesive force F is measured after being placed at 23°C × 50% RH for 0.5 h. B It is 0.5 to 3.5 N / 20 mm, preferably 0.5 to 2 N / 20 mm.

[0154] When the adhesion F B When the adhesive force F falls within the above range, excellent adhesiveness can be achieved. BIf the adhesive force F is less than 0.5N / 20mm, the bonded composite sheet may peel off due to insufficient adhesion. B If it is greater than 3.5 N / 20 mm, it is difficult to peel off from the adherend, the peeling workability is poor, and it is easy to cause adverse effects such as residual adhesive contamination. The above-mentioned adhesive force can be measured by the method described in the examples described below.

[0155] In some preferred embodiments, the adhesive layer is attached to a Cu plate, heated at 200°C for 1 hour, and then placed at 23°C × 50% RH for 0.5 hour to measure the adhesive force F A It is 10 N / 20 mm or less, preferably 5 N / 20 mm or less.

[0156] When the adhesive strength of the adhesive sheet after heating at 220° C. for 15 minutes falls within the above range, excellent adhesive performance can be maintained, excellent adhesion reliability after aging can be achieved, and peelability and handling properties are also excellent. A When it is greater than 10N / 20mm, the adhesive force to the adherend increases, the peeling operation is poor, the adherend is easily damaged during peeling, and residual adhesive pollution is generated after peeling. A For example, it can be measured by the method described in Examples described later.

[0157] In some preferred embodiments, after the adhesive layer is attached to the Cu plate and then peeled off, the surface energy of the Cu plate is 30-40 mN / m. When the surface energy is within the above range, a low-contamination adhesive composite sheet can be provided.

[0158] The surface energy can be measured, for example, by the method described in the Examples described below.

[0159] In some preferred embodiments, the elastic modulus change rate W of the adhesive layer when pressed into 500 nm by nanoindentation method at 23° C. and 100 Hz is B / W A 1.1~3.5,

[0160] Among them, the elastic modulus W A is the elastic modulus of the adhesive layer at 23°C,

[0161] Elastic modulus W B It is the elastic modulus of the adhesive layer at 23°C after being heated at 150°C for 2 hours.

[0162] In the present invention, the elastic modulus change rate is used to characterize the secondary crosslinking of the adhesive layer at high temperature. When the elastic modulus change rate is within the above range, the cohesion of the adhesive layer is increased, thereby improving the heat resistance, while reducing the residual adhesive phenomenon when peeling from the surface of the adhered object, thereby reducing the pollution.

[0163] The elastic modulus can be measured by, for example, the method described in Examples below.

[0164] [Base material layer]

[0165] The material of the base material layer constituting the adhesive composite sheet disclosed herein is not particularly limited and can be appropriately selected according to the purpose and form of use of the adhesive composite sheet.

[0166] As the substrate layer, various film substrates can be preferably used. As the resin material constituting the resin film, for example, polyester, polyolefin (PO), nylon 6, nylon 66, polyamide (PA), polyimide (PI), polyamide-imide (PAI), polyetheretherketone (PEEK), polyethersulfone (PES), polyphenylene sulfide (PPS), polycarbonate (PC), thermoplastic polyurethane (TPU), ethylene-vinyl acetate copolymer (EVA), polytetrafluoroethylene (PTFE) and other fluororesins, acrylic resins, polyacrylates, polystyrene, polyvinyl chloride (PVC), polyvinylidene chloride, cast polypropylene (CPP) and other resins can be used. The above-mentioned resin film can be a film formed using a resin material containing one such resin alone, or a film formed using a resin material blended with more than two kinds of materials. The above-mentioned resin film can be a non-stretched film, or a film stretched (for example, uniaxially stretched or biaxially stretched). Among these, in order to better achieve the effects of the present invention, the substrate layer preferably includes a polyethylene oxide film (PO film), a polyimide film (PI film), a polyethylene terephthalate film (PET film), a polypropylene film (PP film) or a polyethylene film (PE film).

[0167] The method for producing the resin film is not particularly limited, and for example, a conventionally known general resin film forming method such as extrusion forming, inflation forming, T-die casting, calender roll forming, etc. can be appropriately used.

[0168] The surface of the substrate layer of the present invention may be subjected to any surface treatment in order to improve adhesion and retention with adjacent layers, etc. As the surface treatment, for example, chemical or physical treatments such as chromic acid treatment, ozone exposure, flame exposure, high voltage electric shock exposure, ionizing radiation treatment, and coating treatment may be cited.

[0169] The thickness of the substrate layer of the present invention is preferably 2 to 50 μm, depending on the desired strength or flexibility, the intended use, and the like.

[0170] (Method for producing bonded composite sheet)

[0171] The adhesive composite sheet of the present invention can be produced by any appropriate method, for example, a method of coating the adhesive composition on a substrate layer, or a method of transferring a coating layer formed by coating the adhesive composition on any appropriate substrate onto the substrate layer.

[0172] As the coating method of the above-mentioned adhesive composition, any appropriate coating method can be adopted. For example, each layer can be formed by drying after coating. As the coating method, for example, coating methods such as coating using a multi-coater, a die coater, a gravure coater, an applicator, a rod coater, an air knife coating, a reverse roll coating, a lip coating, a dip coating, an offset printing, a flexographic printing, and a screen printing can be cited. As the drying method, for example, natural drying, heat drying, etc. can be cited. The heating temperature in the case of heat drying can be set to any appropriate temperature according to the characteristics of the substance as the drying object.

[0173] (use)

[0174] The bonded composite sheets disclosed herein can be used, for example, in heat-resistant protection or heat-resistant packaging processes, providing excellent heat resistance and low contamination.

[0175] Example

[0176] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. In addition, in the examples, unless otherwise specified, "parts" and "%" are weight references. If no specific conditions are specified in the examples, the conditions are carried out under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the materials or instruments used are conventional products that can be obtained commercially.

[0177] <Preparation of acrylic polymer>

[0178] Production Example 1

[0179] Into a reaction container equipped with a stirrer, a thermometer, a nitrogen inlet tube and a reflux condenser, 89 parts of 2-ethylhexyl acrylate (2-EHA), 2 parts of 2-hydroxyethyl acrylate (HEA), 4 parts of acrylic acid (AA), 5 parts of ethylene urea ethoxy methacrylate (WAMX), and 200 parts of ethyl acetate as a polymerization solvent were added, and after stirring at 65° C. for 1.5 hours under a nitrogen atmosphere, 0.3 parts of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the reaction was carried out at 65° C. for 4 to 5 hours to obtain a solution of acrylic polymer A1.

[0180] Production Examples 2 to 6

[0181] Acrylic polymers A2 to A6 were prepared in the same manner as acrylic polymer A1 except that the types and amounts of monomer components were changed as shown in Table 1.

[0182] Comparative Manufacturing Examples 1 to 4

[0183] Acrylic polymers C1 to C4 were prepared in the same manner as acrylic polymer A1 except that the types and amounts of monomer components were changed as shown in Table 2.

[0184] Table 1

[0185]

[0186] Table 2

[0187]

[0188] <Production of Bonded Composite Sheet>

[0189] Example 1

[0190] To the solution of acrylic polymer A1 prepared in Production Example 1, 2 parts of butylated melamine-formaldehyde resin (produced by BSAF) as a crosslinking agent were added based on 100 parts of acrylic polymer A1 contained in the solution, and the mixture was uniformly mixed to prepare an adhesive composition B1.

[0191] The adhesive composition B1 was applied on one side of a PI film having a thickness of 25 μm as a substrate layer, and then heated at 120° C. for 3 minutes to form an adhesive layer having a thickness of 8 μm, and then a PET release film was attached to the adhesive layer.

[0192] The evaluation results are shown in Table 3.

[0193] Example 2

[0194] To the solution of acrylic polymer A2 prepared in Production Example 2, 2 parts of benzoguanamine (manufactured by Cytec) as a crosslinking agent were added based on 100 parts of acrylic polymer A2 contained in the solution, and the mixture was uniformly mixed to prepare a pressure-sensitive adhesive composition B2.

[0195] The adhesive composition B2 was applied to one side of a PI film having a thickness of 25 μm as a substrate layer, and then heated at 120° C. for 3 minutes to form an adhesive layer having a thickness of 8 μm. Thus, an adhesive composite sheet was obtained. The evaluation results are shown in Table 3.

[0196] Embodiments 3 to 6

[0197] An adhesive composite sheet was obtained in the same manner as in Example 2 except that the type of acrylic polymer, the type and the amount of the crosslinking agent used were changed as shown in Table 3. Table 3 shows the evaluation results.

[0198] Comparative Examples 1 to 4

[0199] An adhesive composite sheet was obtained in the same manner as in Example 2 except that the type of acrylic polymer, the type and the amount of the crosslinking agent used were changed as shown in Table 4. The evaluation results are shown in Table 4.

[0200] Comparative Example 5

[0201] A silicone rubber product TRA6034C (manufactured by Nitto Denko (Shanghai Songjiang) Co., Ltd.) was applied to one side of a PI film having a thickness of 25 μm as a substrate layer to form an adhesive layer having a thickness of 8 μm. Thus, an adhesive composite sheet was obtained. The evaluation results are shown in Table 4.

[0202] Table 3

[0203]

[0204] L-75C: Polyisocyanate crosslinker, manufactured by Wanhua Chemical Group Co., Ltd.

[0205] Table 4

[0206]

[0207] <Evaluation Test>

[0208] (1) Surface energy of adhesive layer at 23°C

[0209] The test fluid was distilled water.

[0210] Test instrument: KRUSS, contact angle analyzer model DSA100

[0211] Specifically, the acrylic polymer was evenly coated on the SUS403BA plate with a coating thickness of 8 μm and dried at 120° C. for 3 min. In a test environment of 23° C. and 50% RH, the test sample plate prepared above was placed on the test platform of the contact angle analyzer, and the test liquid was dropped on the polymer surface to test the surface energy.

[0212] (2) Adhesion F B (Adhesive layer was bonded to a Cu plate and the adhesive strength was measured at 23°C)

[0213] The adhesive composite sheets produced in the respective Examples and Comparative Examples were used as test pieces.

[0214] Under the standard environment of 23°C and 50%RH, the release liner covering the adhesive surface of each test piece was peeled off, and a 2 kg roller was reciprocated once to press the exposed adhesive surface onto the adherend (Cu plate). After the test piece pressed onto the adherend by the operation was placed under the standard environment for 30 minutes, it was peeled off at a tension speed of 300 mm / min and a peeling angle of 180° using a tensile testing machine (manufactured by Shimadzu Corporation, product name "Tensilon") according to JIS Z0237, and the force required for the peeling (180° peeling adhesive force) (N / 20mm) was measured.

[0215] (3) Adhesion F A (The adhesive layer was attached to a Cu plate, heated at 200°C for 1 hour, and then the adhesive strength was measured at 23°C)

[0216] The adhesive composite sheets produced in the respective Examples and Comparative Examples were used as test pieces.

[0217] Under a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test piece was peeled off, and the exposed adhesive surface was pressed against an adherend (Cu plate) by reciprocating a 2 kg roller once, and then heated in an oven at 200°C for 1 hour. The test piece pressed against the adherend in this manner was left under the above standard environment for 30 minutes, and then peeled at a tensile speed of 300 mm / min and a peeling angle of 180° using a tensile tester (manufactured by Shimadzu Corporation, product name "Tensilon") according to JIS Z 0237, and the force required for the peeling (180° peeling adhesive force) (N / 20 mm) was measured.

[0218] (4) Ultraviolet absorption peak point (the ultraviolet absorption peak point of the bonding composite sheet in the wavelength range of 250 to 300 nm)

[0219] Sample treatment: 1 g of sample (the adhesive layer of the adhesive composite sheet prepared in each embodiment and each comparative example) was soaked in 30 mL of alcohol for 36 h, and the mixed solution of alcohol and extract was tested by UV;

[0220] Test instrument: UV-visible spectrophotometer, model U-3900, manufacturer HITACHI

[0221] Measurement type: Wavelength scan

[0222] Data Mode: Abs

[0223] Starting wavelength: 800.00nm

[0224] End wavelength: 190.00nm

[0225] Scanning speed: 300 nm / min

[0226] Sampling interval: 1.00nm

[0227] (5) Thermal weight loss (thermal weight loss of adhesive layer at 200°C)

[0228] Testing instrument: Waters Technology Co., Ltd., thermogravimetric analyzer model: TGA550;

[0229] Test conditions: nitrogen protection, temperature rise from 23℃ to 200℃, ramp 10℃ / min, test thermal weight loss at 200℃. Ramp 10℃ / min; constant temperature 240.0min; mass flow rate 200mL / min.

[0230] (6) Gel fraction (the gel fraction of the adhesive layer measured at 23°C after heating at 150°C for 2 hours)

[0231] Heat the naturally dried adhesive layer in an oven at 150°C for 2 hours, take a sample of weight m1 (0.5-1.0g) and put it into a 50mL glass bottle, soak it in toluene for 1 week. Filter the soaking mixture with filter paper (product name: NTF-1122), and dry the remaining residue at 120°C and weigh m2.

[0232] Gel fraction = (m1-m2) / m1*100%

[0233] (7) Surface energy of the Cu substrate (surface energy of the Cu substrate after the adhesive layer is attached to the Cu substrate and then peeled off)

[0234] The test fluid was distilled water.

[0235] Test instrument: KRUSS, contact angle analyzer model DSA100

[0236] Specifically, under a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test piece (the adhesive composite sheet prepared in each embodiment and each comparative example) was peeled off, and the exposed adhesive surface was pressed against the adherend (Cu plate) by a 2 kg roller reciprocating once, and then placed in a 200°C oven for heating for 1 hour. After the test piece pressed against the adherend in this way was placed under the above standard environment for 30 minutes, it was peeled off according to JIS Z 0237 using a tensile tester (manufactured by Shimadzu Corporation, product name "Tensilon") at a tensile speed of 300 mm / min and a peeling angle of 180°. The peeled Cu plate was placed on a contact angle analyzer test platform with the peeled surface facing upward, and the test liquid was slowly dripped on the surface of the Cu plate to test the surface energy.

[0237] (8) Elastic modulus

[0238] Nanoindentation measurement of the pressure-sensitive adhesive layer surface was performed using a nanoindenter (trade name: "TriboIndenter", manufactured by HYSITRON Inc.) under the following conditions.

[0239] Use indenter: Berkovich (triangular cone type)

[0240] Measurement method: Single indentation measurement

[0241] Measurement temperature: 23°C Frequency: 100Hz

[0242] Indentation depth setting: 500nm

[0243] Load: 1mN

[0244] Load speed: 0.1mN / s

[0245] Unloading speed: 0.1mN / s

[0246] Hold time: 1s

[0247] Specifically, in a test environment of 23° C. and 50% RH, after peeling off the release layer of the adhesive layer of the adhesive composite sheet, the nanoindenter test platform is placed with the adhesive layer facing the test area, and the test is performed according to the above test conditions.

[0248] (9) Pollution

[0249] The pressure-sensitive adhesive sheets prepared in the respective Examples and Comparative Examples were used as test pieces.

[0250] Under a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test piece was peeled off, and the exposed adhesive surface was pressed against the adherend C26000 copper plate by a 2 kg roller reciprocating once, and then placed in a 200°C oven for heating for 1 hour. After the test piece pressed against the adherend in this manner was placed under the above standard environment for 30 minutes, it was peeled off at a tensile speed of 300 mm / min and a peeling angle of 180° using a tensile testing machine (manufactured by Shimadzu Corporation, product name "Tensilon") according to JIS Z 0237, and the residual adhesive on the adherend was observed.

[0251] ○: No residual glue

[0252] △: The residual adhesive area is greater than 0 and less than 10%

[0253] ×: The residual adhesive area is more than 10%

[0254] (10) Printability

[0255] The pressure-sensitive adhesive sheets prepared in the respective Examples and Comparative Examples were used as test pieces.

[0256] Under the standard environment of 23°C and 50%RH, the peeling liner covering the adhesive surface of each test piece was peeled off, and the exposed adhesive surface was pressed to the adherend C26000 copper plate by a 2kg roller back and forth once, and then placed in a 200°C oven for heating for 1h. After the test piece pressed to the adherend by such operation was placed under the above standard environment for 30 minutes, the adhesive sheet on the copper plate was peeled off using a tensile testing machine (manufactured by Shimadzu Corporation, product name "Tensilon") according to JIS Z 0237 at a tensile speed of 300mm / min and a peeling angle of 180°. 0.5g of white standard ink was applied to the peeled copper plate with an ink knife, with a coating thickness of 0.2μm±0.05, and the ink was left to stand for 3min to observe the ink shrinkage area.

[0257] ○: Shrinkage area is less than 5%

[0258] △: Shrinkage area is 5 to 20%

[0259] ×: Shrinkage area greater than 20%

[0260] (11) Encapsulation resin permeability

[0261] The pressure-sensitive adhesive sheets prepared in the respective Examples and Comparative Examples were used as test pieces.

[0262] Under a standard environment of 23°C and 50% RH, peel off the liner covering each test piece, and press the exposed adhesive surface onto the test template (C26000 copper plate with a length of 5.5cm, a width of 5.5cm, and a thickness of 0.1mm, and a hollow square of 0.5cm*0.5cm) by moving a 2kg roller back and forth once, and then leave it for 30 minutes. Place the side with the adhesive composite sheet facing down on a horizontal heating plate, and use a scraper to apply epoxy resin (trade name "HC-300B6", manufactured by Nitto Denko) on the other side of the test template with a coating thickness of 0.5 to 1.0mm. Heat the test template treated as above at 175°C for 90s, cool to 23°C, and combine with Figure 2 Observe the resin leakage on one side of the bonded composite sheet.

[0263] ○: No resin leakage

[0264] △: 1 to 2 hollows with resin leakage

[0265] ×: 3 to 16 hollows have resin leakage

[0266] (12) Comprehensive evaluation

[0267] Based on the above evaluation results, a comprehensive evaluation was performed according to the following criteria.

[0268] ○: All evaluation items are "○"

[0269] △: There is no "×" in the evaluation items, but there is at least one "△"

[0270] ×: There are 1 or more "×" in the evaluation items

[0271] It can be seen from Table 3 that the evaluation results of the contamination, printability (ink) and encapsulation resin permeability of the adhesive composite sheets of Examples 1 to 6 are all excellent. The composite sheets have excellent high temperature resistance and will not cause residual adhesive contamination to the adherends. They can be well used in heat-resistant application fields such as heat-resistant protection or heat-resistant encapsulation processes.

[0272] As shown in Table 4, the adhesive composite sheets of Comparative Examples 1 to 5 have poor evaluation results in at least one of contamination, printability (ink) and encapsulation resin permeability, and cannot be used in heat-resistant application fields such as heat-resistant protection or heat-resistant encapsulation processes.

[0273] Industrial Applicability

[0274] The adhesive composite sheet of the present invention not only has excellent adhesion and heat resistance, but also does not produce residual adhesive pollution to the adherend, has excellent peelability and operability, and can be well used in heat-resistant application fields such as heat-resistant protection or heat-resistant packaging processes.

Claims

1. A bonding composite sheet, characterized in that: It comprises an adhesive layer, The ultraviolet absorption peak of the adhesive composite sheet in the wavelength region of 250 to 300 nm is less than 0.22 abs. The change rate F of the peeling adhesive force of the adhesive layer to the Cu plate at 180° and 300 mm / min tensile speed A / F B is less than 2, Among them, F A The adhesive strength is measured at 23°C after the adhesive layer is attached to a Cu plate and heated at 200°C for 1 hour. F B The adhesive layer is bonded to a Cu plate and the adhesive strength is measured at 23°C.

2. The adhesive composite sheet according to claim 1, characterized in that: The surface energy of the adhesive layer at 23° C. is 20 to 30 mN / m.

3. The adhesive composite sheet according to claim 1 or 2, characterized in that: The adhesive layer is formed of an adhesive composition, The adhesive composition comprises a base polymer, which comprises, based on 100 parts by weight of all monomer components of the base polymer, 70 to 90 parts by weight of a soft monomer, 5 to 20 parts by weight, preferably 5 to 10 parts by weight of a monomer represented by the following formula (a) or by the following formula (b), and 5 to 12 parts by weight of a functional monomer. In formula (a), X1 represents -NH-R, wherein R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms; A means that the terminal group contains a C=C side chain; In formula (b), X2 represents -NH; A represents a side chain having one C=C at the terminal group.

4. The adhesive composite sheet according to claim 3, characterized in that: The base polymer satisfies any one of the following conditions (i) to (iii): (i) the soft monomer is a (meth)acrylate monomer represented by the following formula (c) having a glass transition temperature of -80 to -10°C, In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms, Y represents a hydrogen atom or a methyl group; (ii) the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-hydroxymethylmethacrylamide and 2-[[(butylamino)-carbonyl]oxy]ethyl 2-acrylate, The monomer represented by formula (b) comprises 2-acrylic acid-2-(2-oxo-1-imidazolinyl)ethyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)ethyl ester, 2-acrylic acid-2-(2-oxo-1-imidazolinyl)propyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)propyl ester, 2-acrylic acid-2-(2-oxo-1-imidazolinyl)butyl ester, 2-methyl-2-acrylic acid-2-(2-oxo-1-imidazolinyl)butyl ester, N-[2- at least one of the group consisting of 2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)ethyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)propyl]-2-acrylamide, N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide and 2-methyl-N-[2-(2-oxo-1-imidazolidinyl)butyl]-2-acrylamide; (iii) the functional monomer comprises a (meth)acrylate monomer containing a hydroxyl group and / or a (meth)acrylate monomer containing a carboxyl group, The hydroxyl-containing (meth)acrylate monomer comprises at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate, The carboxyl-containing (meth)acrylate monomer comprises at least one selected from the group consisting of (meth)acrylic acid, (iso)butylene acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate and 2-carboxypentyl (meth)acrylate.

5. The adhesive composite sheet according to claim 3, characterized in that: The adhesive composition further includes a cross-linking agent; Preferably, based on 100 parts by weight of the base polymer, the content of the crosslinking agent is 2 to 20 parts by weight, preferably 2 to 15 parts by weight. Preferably, the cross-linking agent comprises an amino resin cross-linking agent.

6. The adhesive composite sheet according to claim 1 or 2, characterized in that: The adhesive composite sheet satisfies any one of the following conditions (iv) to (viiii): (iv) the thermal weight loss of the adhesive layer at 200° C. is 1.0% or less, preferably 0.6% or less; (v) the adhesive layer has a gel fraction of 20 to 70% when measured at 23° C. after being heated at 150° C. for 2 hours; (vi) The adhesive layer is bonded to a Cu plate and left at 23°C x 50% RH for 0.5 h and then the adhesive strength F is measured. B 0.5-3.5N / 20mm, preferably 0.5-2N / 20mm; (vii) The adhesive layer is attached to a Cu plate, heated at 200°C for 1 hour, and then placed at 23°C x 50% RH for 0.5 hour to measure the adhesive strength F. A 10N / 20mm or less, preferably 5N / 20mm or less; (viii) after the adhesive layer is attached to the Cu plate and peeled off, the surface energy of the Cu plate is 30 to 40 mN / m; (viiii) The elastic modulus change rate W of the adhesive layer when pressed into 500 nm by nanoindentation at 23° C. and 100 Hz B / W A 1.1~3.5, Among them, the elastic modulus W A is the elastic modulus of the adhesive layer at 23°C, Elastic modulus W B It is the elastic modulus of the adhesive layer at 23°C after being heated at 150°C for 2 hours.

7. The adhesive composite sheet according to claim 1 or 2, characterized in that: The thickness of the adhesive layer is 2 to 200 μm.

8. The adhesive composite sheet according to claim 1 or 2, characterized in that: The adhesive composite sheet further includes a substrate layer, the substrate layer being disposed on one side of the adhesive layer; The substrate layer includes a polyethylene oxide film (PO film), a polyimide film (PI film), a polyethylene terephthalate film (PET film), a polypropylene film (PP film) or a polyethylene film (PE film); The thickness of the substrate layer is 2 to 50 μm.